Problems encountered in measurement of human tympanic membrane using time averaged holography - MV, Raghavan (Journal of All India Institute of Speech and Hearing)
During the study of vibration of human tympanic membrane using timeaveraged holography, the problems like stability of the object, coating of membrane, and measurement of intensities of laser light were encountered. This paper reports steps taken to overcome these problems in order to obtain clear and consistent holograms. Further, the factors like intensity of illumination, resolution of holographic plates, exposure time are briefly discussed in relation to the authors’ work